airConn: A framework for tiered services in public wireless LAN hot spots - ACHARYA, A. (Institutional Knowledge at Singapore Management University, 2004)
Access to the data services via wireless LANs at private and public hot spot sites is becoming commonplace. The goal of the airConn project is to define an architecture and a prototype implementation that enable the provision of premium and non-premium service tiers for both transient and nontransient users of wireless hot spots. airConn provides for dynamic renegotiation of service tiers and facilitates various billing modes. Thus, it enables service providers to increase their revenue opportunities via multiple flexibility manageable service offerings.